Pengembangan Model Capacitated Maximal Covering Location Problem (CMCLP) Dalam Penentuan Lokasi Pendirian Gudang - Putu Eka Dewi Karunia Wati; Hilyatun Nuha (Department Industrial Engineering, University of Muhammadiyah Malang, 2018)
A strategic location is a place for facility location that built and is able to give maximum advantages for the company. The problem of deciding location is important in optimization area. In general, the solution of that problem focuses on facility placement that is able to minimize or maximizing distribution time, distance, transportation cost or another parameter. Therefore, an appropriate model is needed to determine the strategic location of warehouse establishment. The purpose of this research is to develop a Capacitated Maximal Covering Location Problem (MCLP) model that can be used in determining the location of warehouse establishment that can maximize the number of demands that can be served. From the model, the company not only finds the optimum location to establish the facility but also they can know the number of goods allocated from the distribution center to each demand point as well as the maximum number of demand that can be served.